Arylhydrazines: novel and versatile electrophilic partners in cross-coupling reactions. Issue 59 (1st October 2018) - Hosseinian, Akram; Mohammadi, Robab; Ahmadi, Sheida; Monfared, Aazam; Rahmani, Zahra
Abstract : Arylhydrazines are extremely valuable compounds in organic chemistry that are widely used for the synthesis of a variety of biologically active molecules such as indoles, indazoles, pyrazoles, aryltriazoles, β-lactams and quinazolines. Abstract : Arylhydrazines are extremely valuable compounds in organic chemistry that are widely used for the synthesis of a variety of biologically active molecules such as indoles, indazoles, pyrazoles, aryltriazoles, β-lactams and quinazolines. These compounds have also been widely utilized as arylation agents in oxidative cross-coupling reactions. In this review, we will highlight the most important explorations and developments in the carbon–carbon and carbon–heteroatom (nitrogen, phosphorus, sulfur, and selenium) cross-coupling of arylhydrazines. The literature has been surveyed from 2001 to June 2018.